Maternal and Perinatal Outcomes of COVID-19 in Pregnant Women : Luaran Maternal dan Perinatal pada Ibu Hamil dengan COVID-19 - Putu H. I. Pramana; Gede B. S. Wirawan; Made Y. D. Astiti; Kaspan (Indonesian Socety of Obstetrics and Gynecology, 2021)
Objective: To describe and identify risk factors of maternal and perinatal outcome of COVID-19 in pregnant women.Methods: Literature search was conducted on MEDLINE and Google Scholar databases for articles published in December 2020 to January 2021. Keywords used includes ‘COVID-19’, ‘pregnant women’, ‘maternal outcome’ and ‘fetal outcome.’ Critical appraisal and selection were conducted to identify articles that fulfill inclusion criteria. The selected articles were analyzed thematically to answer the research questions.Results: Literature search yielded 124 articles with 11 included in final analysis. The results showed low to moderate risk of maternal and perinatal adverse outcomes, including low risks for maternal and perinatal mortality coupled with moderate risk for maternal ICU admission and preterm birth with NICU admission for the newborn. Higher risk was observed for pregnant women with symptomatic COVID-19 infection, which points to the necessity for awareness of the risk and targeted early detection efforts.Conclusion: There are low risk for adverse maternal and perinatal outcomes, including mortality and ICU/NICU admission, associated with COVID-19 infection in pregnant women. Risk factors for adverse outcomes included pregnant women with symptomatic COVID-19 infection.Keywords: COVID-19, ICU, maternal mortality, NICU, perinatal mortality, preterm birth Abstrak Tujuan: Mendeskripsikan dan mengidentifikasi faktor risiko luaran maternal dan perinatal COVID-19 pada ibu hamil.Metode: Penelusuran literatur dilakukan di database MEDLINE dan Google Scholar untuk artikel yang diterbitkan pada Desember 2020 hingga Januari 2021. Kata kunci yang digunakan meliputi 'COVID-19', 'wanita hamil', 'keluaran ibu' dan 'hasil janin'. Penilaian dan seleksi kritis dilakukan untuk mengidentifikasi artikel yang memenuhi kriteria inklusi. Artikel yang dipilih dianalisis secara tematis untuk menjawab pertanyaan penelitian.Hasil: Penelusuran literatur menghasilkan 124 artikel dengan 11 termasuk dalam analisis akhir. Hasil penelitian menunjukkan risiko rendah hingga sedang untuk luaran buruk maternal dan perinatal, termasuk risiko rendah untuk kematian maternal dan perinatal ditambah dengan risiko sedang untuk masuk ICU ibu dan kelahiran prematur dengan masuk NICU untuk bayi baru lahir. Risiko yang lebih tinggi diamati untuk wanita hamil dengan infeksi COVID-19 bergejala, yang menunjukkan perlunya kesadaran akan risiko dan upaya deteksi dini yang ditargetkan.Kesimpulan: Terdapat risiko rendah untuk laran buruk maternal dan perinatal, termasuk kematian dan rawat inap di ICU/NICU, terkait dengan infeksi COVID-19 pada wanita hamil. Faktor risiko untuk luaran buruk adalah wanita hamil dengan gejala infeksi COVID-19.Kata kunci: COVID-19, ICU, kelahiran preterm, mortalitas maternal, mortalitas perinatal, NICU